Levels of Cognitive Domain of Tasks in English Textbooks for Senior High School: A Revised Bloom’s Taxonomy Analyses - Rustiyani, Rustiyani; Sofyan, Dedi; Syafryadin, Syafryadin (English Education: Jurnal Tadris Bahasa Inggris, 2021)
This study is a descriptive qualitative which aims to know the appropriateness of the textbook’s content with the cognitive dimension of Revised Bloom’s Taxonomy and to know the dominant cognitive category of the Revised Bloom’s Taxonomy in the textbook. This research was focused on analyzing the English Textbook, “Pathway to English”, which is published by Erlangga. The data was analyzed through data analysis table to categorize the activity with defined as any one of the following: a question or instructional activity, based on cognitive dimension. The result showed that there are 271 activities in the textbook. The activities spread over 105 (38.7%) remembering, 76 (28%) understanding, 48 (17.7%) applying, 28 (10.3%) analyzing, 7 (2.6%) evaluating, and 7 (2.6%) creating. The total number of activities that included to HOTS are 42 activities or 15.5% and the activities that included to LOTS are 229 activities or 84.5%. The most dominant activity was remembering which the lowest dimension of cognitive level of Revised Bloom Taxonomy. Then, the number of LOTS and HOTS activities in each chapter are very different. Hence, it is not enough if the teacher just only uses the English textbook as a teaching tool to improve students HOTS ability.